Емоційне поле вигуків як проблема лексикографічного подання - Фейхун, Лю; Liu, Feihоng (Волинський національний університет імені Лесі Українки, 2012)
У статті розглянуто види вигуків згідно з їх значенням та засоби їх тлумачення у словнику. The article deals with the types of interjections in accordance with their meaning and the ways of their explanation in a dictionary.
Emotional Field of Interjections as a Problem of Lexicographic Presentation
Keywords: вигук; interjection; словник; dictionary; тлумачення; explanation